2003
DOI: 10.1007/s00068-003-1285-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Outcome of Gunshot Injuries in a Civilian Population in West Africa

Abstract: Background and Objectives: Gunshot injuries (GSI) were first reported in West Africa following the Nigerian civil war of [1967][1968][1969][1970]. Recent wars within and around the West African subregion have further encouraged easy access to sophisticated and locally manufactured firearms. This report examines the epidemiology and management of GSI in an urban settlement in West Africa. Patients and Methods: GSI data was collected prospectively for 24 months beginning September 1999: age, sex, velocity of gun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 11 publications
5
19
3
Order By: Relevance
“…No deaths occurred among the 12 patients injured by SALW, but many were left with disabilities (66%). As with other studies, most victims of SALW were males (7,19). Their median hospital stay was 21 days.…”
Section: S T U D Y I N G S a Lw: K A N O N O R T H E R N N I G E R I Amentioning
confidence: 72%
See 2 more Smart Citations
“…No deaths occurred among the 12 patients injured by SALW, but many were left with disabilities (66%). As with other studies, most victims of SALW were males (7,19). Their median hospital stay was 21 days.…”
Section: S T U D Y I N G S a Lw: K A N O N O R T H E R N N I G E R I Amentioning
confidence: 72%
“…Amnesty International and other organizations have consistently called for action to end indiscriminate police use of SALW (15). A 2003 study in Ilorin found that after armed robbery, the police were the second most common cause of injuries due to SALW (19).…”
Section: Military History and Police Presencementioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18]26] Hospital rates of trauma admissions resulting from GSIs have been reportedly variable in Nigeria depending on the socio-economic, religious, cultural, and political activities in the locality. [13,21,27] The reported hospital rates were 4.5%, [13] 3.6%, [21] and 3.8% [27] in some Nigerian studies. Studies have also described the sites of GSIs to involve head and neck, [10] oro-facial region, [28] upper extremities, [29] chest, [30] and lower extremities.…”
Section: Introductionmentioning
confidence: 86%
“…16 wars in and around west African region have increased easy acquisition to sophisticated and locally manufactured firearms leading to increased incidence of gunshot injuries in peace times through armed violence. 17 This study is taken to document our experience and associated consequences with respect to morbidities due to gunshot injuries in order to advance ways of curbing the growing trends. Materials and Method: A cross-section of all autopsies done from 2008-2012 was evaluated and that due to gunshot deaths were extracted from the medico-legal (coroner) files.…”
Section: Introductionmentioning
confidence: 99%